Thermal power plant simulation and control - Flynn, Damian (Institution of Engineering and Technology, 2003)
The book reviews developments in the following fields: advances in power plant technology; power plant modelling; pulverised fuel coal mill modelling and control; generator excitation control; steam temperature control; supervisory predictive control of a combined cycle thermal power plant; multivariable power plant control; plant load-following capability; NOx emission modelling in coal-fired plant; model-based fault detection in a high-pressure heater line; data mining for performance monitoring and optimisation; advanced plant management systems; physical model-based coordinated power plant control; and power plant operations management.